Optimizing Fruit Nutrition Data Presentation for Improved User Experience in the RSPG-Burapha Ecosystem - Sootanan, Pitak; Petchlert, Chatchawin (Journal of Applied Informatics and Technology, 2025)
Nutrition facts enable consumers to clearly understand the nutritional content of each type of fruit, empowering them to make informed decisions when purchasing and consuming food. This article presents practical guidelines for developing and enhancing fruit nutrition data display within the RSPG-Burapha learning ecosystem. Our research was meticulously designed and developed user-friendly and efficient fruit nutrition data display tools. These tools were then rigorously evaluated for their effectiveness and user satisfaction, ensuring the practicality and relevance of our research to the end users. Our study delved into the nutrition of 75 Eastern Thai fruits, illustrating at least 20 varieties and detailing product info for 141 types. The database homepage features an engaging motion graphic to easily explore organized fruit and product data. Detailed nutrition facts, radar charts for comparisons, bar charts, and hierarchical clustering for analysis are provided, along with categorizing fruit products by groups. The database received overwhelmingly positive satisfaction ratings from 476 respondents, a testament to the impact of our work on improving user satisfaction and nutritional information accessibility. The research emphasizes the significance of improving the presentation of nutrition data to facilitate informed choices in maintaining a balanced and healthy diet within the RSPG-Burapha learning ecosystem, with access to this database provided through the website https://fruit.rspgburapha.com/.